Does Pseudomonas aeruginosa Colonization Affect Exercise Capacity in CF? - Asterios Kampouras; Elpis Hatziagorou; Vasiliki Avramidou; Vasiliki Georgopoulou; Fotios Kirvassilis; John Tsanakas (Pulmonary Medicine)
Introduction. Cardio-Pulmonary Exercise Testing (CPET) has been recognized as a valuable method in assessing disease burden and exercise capacity among CF patients. Aim. To evaluate whether Pseudomonas aeruginosa colonization status affects Exercise Capacity, LCI and High-Resolution Computed Tomography (HRCT) indices among patients with CF; to check if Pseudomonas colonization can predict exercise intolerance. Subjects. Seventy-eight (78) children and adults with CF (31 males) mean (range) age 17.08 (6.75; 24.25) performed spirometry, Multiple Breath Washout (MBW) and CPET along with HRCT on the same day during their admission or follow up visit. Results. 78 CF patients (mean FEV1: 83.3% mean LCI: 10.9 and mean VO2 peak: 79.1%) were evaluated: 33 were chronically colonized with Pseudomonas aeruginosa, 24 were intermittently colonized whereas 21 were Pseudomonas free. Statistically significant differences were observed among the three groups in: peak oxygen uptake % predicted (VO2 peak% (p<0.001), LCI (p<0.001), as well as FEV1% (p<0.001) and FVC% (p<0.001). Pseudomonas colonization could predict VO2 peak% (p<0.001, r2: −0.395). Conclusion. Exercise capacity as reflected by peak oxygen uptake is reduced in Pseudomonas colonized patients and reflects lung structural damages as shown on HRCT. Pseudomonas colonization could predict exercise limitation among CF patients.